2018
DOI: 10.1002/best.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Torsionstragverhalten eines Segmentturms mit alternativer Fugenausbildung

Abstract: Eine Weiterentwicklung der zurzeit gängigsten Herstellungsart von Segmenttürmen für Windenergieanlagen stellt die veränderte Ausbildung der entstehenden Fugen dar. Die seit vielen Jahren für die Horizontalfugen verwendete Trockenfuge, welche ohne eine Ausgleichsschicht durch Epoxid‐ oder Zementmörtel auskommt, soll auch für die senkrechten Fugen verwendet werden. Die Ebenheit in den Fugen wird über eine hochpräzise CNC‐Fräse hergestellt und dadurch die Dichtigkeit der Konstruktion sowie die flächige Kraftübert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…According to analytical and numerical investigations by Klein and Marx [12]- [14], the introduction of vertical joints results in a significantly more complex joint load-bearing behaviour of the tower structure. Hartwig et al [15] conducted numerical calculations and found that using half-shell segments reduces the torsional load-bearing capacity of the horizontal joint by up to 40% compared to circular ring segments, even when the joint is fully compressed. To better understand these findings, experimental investigations on segmented tower structures with vertical joints are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…According to analytical and numerical investigations by Klein and Marx [12]- [14], the introduction of vertical joints results in a significantly more complex joint load-bearing behaviour of the tower structure. Hartwig et al [15] conducted numerical calculations and found that using half-shell segments reduces the torsional load-bearing capacity of the horizontal joint by up to 40% compared to circular ring segments, even when the joint is fully compressed. To better understand these findings, experimental investigations on segmented tower structures with vertical joints are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Neben Brücken sind auch Windenergieanlagen (WEA) aufgrund der hohen Standardisierungsmöglichkeit der Turmsegmente ein Anwendungsgebiet [5–7]. Beide Bauwerksgruppen werden vorrangig durch nichtruhende, zyklische Belastungen beansprucht.…”
Section: Motivationunclassified